Sztuka epoki paleolitu w świetle hipotezy mózgu społecznego - Wagner, Patrycja (Folia Praehistorica Posnaniensia, 2023)
The purpose of this article is to try to look at the phenomenon of Paleolithic cave art differently – through the prism of the assumptions of the social brain hypothesis. This paper will present the main assumptions of Robin Dunbar’s social brain concept, which assumes that the increase in the size of the social group influenced the development of the individual (both biologically and socio-culturally). Larger communities provided the impetus for the development of new cognitive qualities, which provided the opportunity for art to emerge.